Positron emission tomography of type 2 cannabinoid receptors for detecting inflammation in the central nervous system - Ni, Ruiqing (Acta Pharmacol Sin, 2018)
Cannabinoid receptor CB(2) (CB(2)R) is upregulated on activated microglia and astrocytes in the brain under inflammatory conditions and plays important roles in many neurological diseases, such as Alzheimer’s disease, amyotrophic lateral sclerosis, and ischemic stroke. The advent of positron emission tomography (PET) using CB(2)R radiotracers has enabled the visualization of CB(2)R distribution in vivo in animal models of central nervous system inflammation, however translation to humans has been less successful. Several novel CB(2)R radiotracers have been developed and evaluated to quantify microglial activation. In this review, we summarize the recent preclinical and clinical imaging results of CB(2)R PET tracers and discuss the prospects of CB(2)R imaging using PET.